In vivo imaging of tumour xenografts with an antibody targeting the potassium channel K(v)10.1 - Napp, Joanna (Eur Biophys J, 2016)
The K(v)10.1 (Eag1) voltage-gated potassium channel represents a promising molecular target for novel cancer therapies or diagnostic purposes. Physiologically, it is only expressed in the brain, but it was found overexpressed in more than 70 % of tumours of diverse origin. Furthermore, as a plasma membrane protein, it is easily accessible to extracellular interventions. In this study we analysed the feasibility of the anti-K(v)10.1 monoclonal antibody mAb62 to target tumour cells in vitro and in vivo and to deliver therapeutics to the tumour. Using time-domain near infrared fluorescence (NIRF) imaging in a subcutaneous MDA-MB-435S tumour model in nude mice, we showed that mAb62-Cy5.5 specifically accumulates at the tumour for at least 1 week in vivo with a maximum intensity at 48 h. Blocking experiments with an excess of unlabelled mAb62 and application of the free Cy5.5 fluorophore demonstrate specific binding to the tumour. Ex vivo NIRF imaging of whole tumours as well as NIRF imaging and microscopy of tumour slices confirmed the accumulation of the mAb62-Cy5.5 in tumours but not in brain tissue. Moreover, mAb62 was conjugated to the prodrug-activating enzyme β-D-galactosidase (β-gal; mAb62-β-gal). The β-gal activity of the mAb62-β-gal conjugate was analysed in vitro on K(v)10.1-expressing MDA-MB-435S cells in comparison to control AsPC-1 cells. We show that the mAb62-β-gal conjugate possesses high β-gal activity when bound to K(v)10.1-expressing MDA-MB-435S cells. Moreover, using the β-gal activatable NIRF probe DDAOG, we detected mAb62-β-gal activity in vivo over the tumour area. In summary, we could show that the anti-K(v)10.1 antibody is a promising tool for the development of novel concepts of targeted cancer therapy.